UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MELALUI MODEL PEMBELAJARAN QUESTION STUDENT HAVE - Sugiyanto, Arinta Rara Kirana, (LPPM STKIP PGRI Bandar Lampung, 2019)
Abstract: The problems that were examined in this research relate to learning about mathematics students who is still low. For that reason it is , the purpose of this study is to find an increase in the results of the kind of classroom learning about mathematics through question student have to their students odd semester class viii junior high school Al Azhar 3 Bandar Lampung in year 2018/2019. The research is research class action ( ptk ) on a student viii a junior high school al azhar 3 lampung consisting of 32 students. To know the results the students learn math test luminance the cycle in the form of essai 5 about as many as with an indicator of success when 75 percent the number of students reach kkm = 70. Any test had first tested the validity of and reliabilitasnya , so they could be used as a measuring instrument research. From the test every cycle it is apparent that an increase in the pre learn math students from research to cycle I of 25 % (56 % students completed kkm) and The first cycle to cycle II of 25 % (81 % students completed kkm). Thus indicators finish in the research success in cycle II. So we can conclude that “an increase in the students learn math through learning model question student have on students VIII in the odd semester class viii junior high school Al Azhar 3 Bandar Lampung in year 2018/2019.